LaS / CoS2 bifunctional catalyst based on rare earth heterogeneous interface as well as preparation method and application of LaS / CoS2 bifunctional catalyst
By introducing LaS/CoS2 catalyst with rare earth heterointerfaces into zinc air batteries, the problem of limited performance of zinc air batteries is solved, and efficient and stable catalytic performance and cost-reducing effect is achieved.
Patent Information
- Application Number
- CN202411503603.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The performance of zinc-air batteries is limited by the efficiency of air cathode oxygen reduction (ORR) and oxygen evolution reaction (OER), making it difficult to achieve theoretical energy density and voltage.
By introducing rare earth heterointerfaces, LaS/CoS2 catalysts are prepared, and the electronic structure is adjusted using sulfur vacancy and heterointerfaces to improve catalytic activity.
It significantly improves catalytic performance, reduces costs, and achieves a lower oxygen evolution overpotential and a higher oxygen reduction half-wave potential, which is suitable for industrial applications of zinc air batteries.
Smart Images

Figure CN119461503A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy nanomaterials, and in particular to a LaS / CoS based on rare earth heterogeneous interface. 2 Bifunctional catalyst and its preparation method and application. Background Art
[0002] At present, the energy structure of countries around the world is still dominated by traditional fossil fuels, but fossil fuels are non-renewable, and the large-scale emission of carbon dioxide, a combustion product of fossil fuels, has caused serious environmental problems. The development and use of environmentally friendly renewable energy is the key to solving energy crises and environmental problems. Among them, the capacity and energy density of zinc-air batteries in clean and environmentally friendly metal-air batteries are several times larger than those of the leading batteries on the market. They can be repeatedly charged and discharged, have good stability, higher safety, and lower cost, and have great development potential. However, due to the energy consumption of the battery's own structure and the voltage drop inside the battery during actual use, zinc-air batteries are still difficult to reach the theoretical energy density and theoretical battery voltage. Its performance is mainly limited by the efficiency of air cathode oxygen reduction (ORR) and oxygen evolution reaction (OER), so it is necessary to develop new, low-cost, efficient and stable bifunctional electrocatalysts to accelerate the kinetic process of the entire reaction. Summary of the invention
[0003] In order to overcome the shortcomings of the prior art, the present invention aims to provide a LaS / CoS based on rare earth heterogeneous interface. 2 Bifunctional catalyst and its preparation method and application.
[0004] The present invention proposes to successfully prepare a LaS / CoS by introducing rare earth heterogeneous interfaces to generate sulfur vacancies. 2 Catalyst. First, La was prepared by two-step hydrothermal 2 O 3 / Co(OH)F, and then the successfully prepared La 2 O 3 / Co(OH)F was placed in a tube furnace in an argon atmosphere for sulfurization to obtain LaS / CoS 2 Directly act as a bifunctional electrocatalyst for electrocatalytic oxygen production and oxygen reduction.
[0005] The purpose of the present invention is achieved by at least one of the following technical solutions.
[0006] A LaS / CoS based on rare earth heterointerface 2 The preparation method of the bifunctional catalyst comprises the following steps:
[0007] (1) dissolving a soluble cobalt source, ammonium fluoride and urea in water and heating them to react to obtain Co(OH)F (smooth nanorods);
[0008] (2) Dispersing the Co(OH)F obtained in step (1) in ethanol, then adding hexamethylenetetramine (HMT) and a soluble lanthanum source, stirring to dissolve, and heating to react, to obtain La 2 O 3 / Co(OH)F (nanorods with particles on the surface);
[0009] (3) La obtained in step (2) 2 O 3 / Co(OH)F and sulfur source are placed in the downstream and upstream of the protective gas flow respectively, and fired to obtain LaS / CoS based on rare earth heterogeneous interface. 2 Bifunctional catalyst.
[0010] Preferably, the soluble cobalt source in step (1) is cobalt nitrate;
[0011] Preferably, the molar ratio of cobalt ions, ammonium fluoride and urea in the soluble cobalt source in step (1) is 1-2:3-4:7-8;
[0012] Preferably, the molar volume ratio of cobalt ions to water in the soluble cobalt source in step (1) is 1-2 mmol: 50-100 mL.
[0013] Preferably, the heating reaction time in step (1) is 5 to 8 hours;
[0014] Preferably, the temperature of the heating reaction in step (1) is 90-120°C.
[0015] Preferably, the soluble lanthanum source in step (2) is lanthanum nitrate;
[0016] Preferably, the molar ratio of lanthanum ions to hexamine in the soluble lanthanum source in step (2) is 0.05-0.15:0.15-0.45.
[0017] Preferably, the mass volume ratio of Co(OH)F to ethanol in step (2) is 0.2-0.4 g: 50-100 mL;
[0018] Preferably, the ratio of the mass of the Co(OH)F in step (2) to the molar amount of lanthanum ions in the soluble lanthanum source is 0.2g:0.05-0.15mmoL (e.g., 0.2g:0.05mmoL, 0.2g:0.08mmoL, 0.2g:0.10mmoL, 0.2g:0.12mmoL, 0.2g:0.15mmoL).
[0019] Preferably, the stirring and dissolving in step (2) is carried out at room temperature for 30 to 60 minutes.
[0020] Preferably, the heating reaction time in step (2) is 5 to 8 hours;
[0021] Preferably, the temperature of the heating reaction in step (2) is 160-200°C.
[0022] Preferably, the sulfur source in step (3) is sulfur powder;
[0023] Preferably, the sulfur source in step (3) is 2 O 3 The mass ratio of / Co(OH)F is 5 to 10:1.
[0024] Preferably, the protective gas in step (3) is argon;
[0025] Preferably, the firing temperature in step (3) is 300-450° C., and the firing time is 1.5-2.5 h.
[0026] The LaS / CoS based on rare earth heterogeneous interface prepared by the above preparation method 2 Bifunctional catalyst.
[0027] The above-mentioned LaS / CoS based on rare earth heterogeneous interface 2 Application of bifunctional catalysts in electrocatalytic oxygen evolution and oxygen reduction.
[0028] LaS / CoS of the present invention 2 Catalysts are introduced into the rare earth interface of transition metal sulfides. Since Co (1.88) has a greater electronegativity than La (1.10), S atoms preferentially bond with Co atoms at the heterojunction interface, resulting in the formation of sulfur vacancies in the La lattice, thereby forming rich sulfur vacancies and providing more active sites. At the same time, the poorly crystalline LaS and the highly crystalline CoS 2 The formation of heterojunction interfaces regulates the electronic structure and promotes the 2 It can enhance the adsorption and electron transfer of oxygen, increase the specific surface area and enrich the pore structure, promote ion transport, improve the tolerance to volume changes, and improve the oxygen electrocatalytic activity.
[0029] The non-precious metal catalyst prepared by the method of the present invention is applied to electrocatalytic oxygen evolution and oxygen reduction reactions, and has high catalytic activity and good stability. The catalytic material has been proven to be promising for industrial zinc-air battery cathode catalyst, thereby greatly improving the theoretical performance of zinc-air batteries.
[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0031] (1) The heterogeneous interface formed by introducing rare earth interfaces in the present invention not only regulates the electronic structure of cobalt, increases the number of mesopores in the material, and increases the specific surface area, but also forms abundant sulfur vacancies, and the catalytic performance of the catalyst introduced with the rare earth interface is significantly improved; the present invention uses non-precious metal-based catalysts to replace the commonly used precious metal catalysts on the market, thereby reducing the cost of the catalyst.
[0032] (2) Heterojunction LaS / CoS prepared by the present invention 2 The catalyst has a low oxygen evolution overpotential and a high oxygen reduction half-wave potential, exhibits good catalytic performance and stability, and has broad application prospects in the field of zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 X-ray diffraction (XRD) pattern;
[0034] Figure 2 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 N 2 Adsorption / desorption curves;
[0035] Figure 3 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 NL-DFT pore size distribution curve;
[0036] Figure 4 is 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 EPR spectrum of
[0037] Figure 5 0.10-LaS / CoS of Example 2 2 Scanning electron microscope (SEM) images of
[0038] Figure 6 is a scanning electron microscope (SEM) image of LaS of Comparative Example 1;
[0039] Figure 7 CoS of Comparative Example 2 2 Scanning electron microscope (SEM) images of
[0040] Figure 8 0.10-LaS / CoS of Example 22 Transmission electron microscopy (TEM) images of
[0041] Fig. 9 0.10-LaS / CoS of Example 2 2 High-resolution transmission electron microscopy (HRTEM) images of
[0042] Fig.10 is a transmission electron microscope (TEM) image of LaS of Comparative Example 1;
[0043] Fig.11 is a high resolution transmission electron microscopy (HRTEM) image of LaS of Comparative Example 1;
[0044] Fig.12 CoS of Comparative Example 2 2 Transmission electron microscopy (TEM) images of
[0045] Fig.13 CoS of Comparative Example 2 2 High-resolution transmission electron microscopy (HRTEM) images of
[0046] Fig.14 0.10-LaS / CoS of Example 2 of the present invention 2 , LaS of Comparative Example 1 and CoS of Comparative Example 2 2 Linear sweep voltammogram (LSV) of oxygen reduction reaction;
[0047] Fig.15 0.10-LaS / CoS of Example 2 of the present invention 2 Chronoamperometric response at fixed potential (0.83 V);
[0048] Fig.16 0.10-LaS / CoS of Example 2 of the present invention 2 , LaS of Comparative Example 1 and CoS of Comparative Example 2 2 Linear sweep voltammogram (LSV) of oxygen evolution reaction;
[0049] Fig.17 0.10-LaS / CoS of Example 2 of the present invention 2 At 10 mA cm -2 Chronopotentiometry curve for 38 h at a current density of ;
[0050] Fig.18 0.05-LaS / CoS of Example 1 2 , 0.10-LaS / CoS of Example 2 2 , 0.15-LaS / CoS of Example 3 2 X-ray diffraction (XRD) pattern;
[0051] Fig.19 0.10-LaS / CoS of Example 1 of the present invention 2 , 0.10-LaS / CoS of Example 2 2 , 0.15-LaS / CoS of Example 3 2 Linear sweep voltammogram (LSV) of oxygen reduction reaction;
[0052] Fig. 20 0.10-LaS / CoS of Example 1 of the present invention 2 , 0.10-LaS / CoS of Example 2 2 , 0.15-LaS / CoS of Example 3 2 Linear sweep voltammogram (LSV) of oxygen evolution reaction. DETAILED DESCRIPTION
[0053] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0054] The electrochemical performance test characterization (linear voltammetric sweep test) method of the catalysts prepared in the following examples and comparative examples is:
[0055] 4.0 mg of the catalyst prepared in Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2 was prepared into 1.0 mL of catalyst ink, which was dropped on the surface of the glassy carbon electrode and used as the working electrode for linear voltammetric scanning test after drying.
[0056] All electrochemical measurements were performed at room temperature. The performance of the catalyst was tested using a three-electrode system, with a glassy carbon electrode coated with the catalyst as the working electrode, a platinum wire electrode as the counter electrode, and a silver / silver chloride electrode (filled with a saturated KCl solution) as the reference electrode. The catalyst performance was tested by linear sweep voltammetry (LSV). For the bifunctional catalyst, when testing ORR, the test medium was O 2 Saturated 0.1 M KOH solution; when testing OER, the testing medium is 1 M KOH solution.
[0057] Example 1
[0058] A LaS / CoS 2 The preparation method of the catalyst comprises the following steps:
[0059] In 50 mL HO 2O to dissolve 1.5 mmol Co(NO 3 ) 2 6H 2 O, 3mmol NH 4 F and 7.5mmol urea. The resulting mixture was transferred to a 100mL Teflon-lined stainless steel autoclave and heated in an oven at 110°C for 5h. The particles were collected, washed several times by centrifugation with deionized water and ethanol, and then dried at 60°C overnight to obtain a pink-purple precipitate product, Co(OH)F.
[0060] The prepared Co(OH)F (200 mg) was dispersed in 50 mL of anhydrous ethanol and ultrasonicated for 30 min to form a uniform slurry. Then, 0.15 mmol HMT and 0.05 mmol La(NO) were added. 3 ) 3 ·xH 2 O, stirred at room temperature for 30 min, then transferred to a 100 mL Teflon-lined stainless steel autoclave and heated in an oven at 180 °C for 6 h. The particles were harvested after multiple rinses and centrifugation cycles with deionized water and ethanol, and then dried at 50 °C overnight to obtain 0.05-La 2 O 3 / Co(OH)F.
[0061] Weigh 400 mg of sulfur powder and place it in a porcelain boat. Put La in another porcelain boat. 2 O 3 / Co(OH)F (40 mg), and the two porcelain boats were placed in the upstream and downstream of the tube furnace respectively. The temperature was raised to 450°C at a heating rate of 5°C / min under an argon flow atmosphere, and maintained at 450°C for 2 h. Then the temperature was naturally cooled to room temperature. The resulting black powder was the final catalyst 0.05-LaS / CoS 2 .
[0062] Example 2
[0063] A LaS / CoS 2 The preparation method of the catalyst comprises the following steps:
[0064] In 50 mL HO 2 O to dissolve 1.5 mmol Co(NO 3 ) 2 6H 2 O, 3mmol NH 4 F and 7.5mmol urea. The resulting mixture was transferred to a 100mL Teflon-lined stainless steel autoclave and heated in an oven at 110°C for 5h. The particles were collected, washed several times by centrifugation with deionized water and ethanol, and then dried at 60°C overnight to obtain a pink-purple precipitate product, Co(OH)F.
[0065] The prepared Co(OH)F (200 mg) was dispersed in 50 mL of anhydrous ethanol and ultrasonicated for 30 min to form a uniform slurry. Then, 0.3 mmol HMT and 0.1 mmol La(NO) were added. 3 ) 3 ·xH 2 O, stirred at room temperature for 30 min, then transferred to a 100 mL Teflon-lined stainless steel autoclave and heated in an oven at 180 °C for 6 h. The particles were harvested after multiple rinses and centrifugation cycles with deionized water and ethanol, and then dried at 50 °C overnight to obtain 0.10-La 2 O 3 / Co(OH)F.
[0066] Weigh 400 mg of sulfur powder and place it in a porcelain boat. Put La in another porcelain boat. 2 O 3 / Co(OH)F (40 mg), and the two porcelain boats were placed in the upstream and downstream of the tube furnace respectively. The temperature was raised to 450°C at a heating rate of 5°C / min in an argon flow atmosphere, and maintained at 450°C for 2 h. Then the temperature was naturally cooled to room temperature. The resulting black powder was the final catalyst 0.10-LaS / CoS 2 .
[0067] Example 3
[0068] A LaS / CoS 2 The preparation method of the catalyst comprises the following steps:
[0069] In 50 mL HO 2 O to dissolve 1.5 mmol Co(NO 3 ) 2 6H 2 O, 3mmol NH 4 F and 7.5mmol urea. The resulting mixture was transferred to a 100mL Teflon-lined stainless steel autoclave and heated in an oven at 110°C for 5h. The particles were collected, washed several times by centrifugation with deionized water and ethanol, and then dried at 60°C overnight to obtain a pink-purple precipitate product, Co(OH)F.
[0070] The prepared Co(OH)F (200 mg) was dispersed in 50 mL of anhydrous ethanol and ultrasonicated for 30 min to form a uniform slurry. Then, 0.45 mmol HMT and 0.15 mmol La(NO) were added. 3 ) 3 ·xH 2O, stirred at room temperature for 30 min, then transferred to a 100 mL Teflon-lined stainless steel autoclave and heated in an oven at 180 °C for 6 h. The particles were harvested after multiple rinses and centrifugation cycles with deionized water and ethanol, and then dried at 50 °C overnight to obtain 0.15-La 2 O 3 / Co(OH)F.
[0071] Weigh 400 mg of sulfur powder and place it in a porcelain boat. Put La in another porcelain boat. 2 O 3 / Co(OH)F (40 mg), and the two porcelain boats were placed in the upstream and downstream of the tube furnace respectively. The temperature was raised to 450°C at a heating rate of 5°C / min under an argon flow atmosphere, and maintained at 450°C for 2 h. Then the temperature was naturally cooled to room temperature. The resulting black powder was the final catalyst 0.15-LaS / CoS 2 .
[0072] Comparative Example 1
[0073] A method for preparing a LaS catalyst comprises the following steps:
[0074] 3 mmol HMT and 1 mmol La(NO 3 ) 3 ·xH 2 O was dissolved in 50 mL of anhydrous ethanol, stirred at room temperature for 30 min, and then transferred to a 100 mL Teflon-lined stainless steel autoclave and heated in an oven at 180 °C for 6 h. The particles were harvested after multiple rinses and centrifugation cycles with deionized water and ethanol, and then dried at 50 °C overnight to obtain La 2 O 3 .
[0075] Weigh 400 mg of sulfur powder and place it in a porcelain boat. Put La in another porcelain boat. 2 O 3 (40 mg), and the two porcelain boats were placed in the upstream and downstream of the tube furnace respectively. The temperature was increased to 450 °C at a heating rate of 5 °C / min under an argon flow atmosphere, and maintained at 450 °C for 2 h. Then the temperature was naturally cooled to room temperature. The obtained black powder was the final catalyst LaS.
[0076] Comparative Example 2
[0077] A CoS 2 The preparation method of the catalyst comprises the following steps:
[0078] In 50 mL HO 2 O to dissolve 1.5 mmol Co(NO 3 ) 2 6H 2 O, 3mmol NH4 F and 7.5mmol urea. The resulting mixture was transferred to a 100mL Teflon-lined stainless steel autoclave and heated in an oven at 110°C for 5h. The particles were collected, washed several times by centrifugation with deionized water and ethanol, and then dried at 60°C overnight to obtain a pink-purple precipitate product, Co(OH)F.
[0079] Weigh 400 mg of sulfur powder and place it in a porcelain boat. Put La in another porcelain boat. 2 O 3 / Co(OH)F (40 mg), and the two porcelain boats were placed in the upstream and downstream of the tube furnace respectively. The temperature was raised to 450°C at a heating rate of 5°C / min under an argon flow atmosphere, and maintained at 450°C for 2 h. Then the temperature was naturally cooled to room temperature. The resulting black powder was the final catalyst LaS / CoS 2 .
[0080] Data Analysis:
[0081] Figure 1 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 X-ray diffraction (XRD) pattern;
[0082] Figure 2 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 N 2 Adsorption / desorption curves;
[0083] Figure 3 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 NL-DFT pore size distribution curve;
[0084] Figure 4 is 0.10-LaS / CoS of Example 2 2 , LaS of Comparative Example 1, CoS of Comparative Example 2 2 EPR spectrum of
[0085] Figure 5 0.10-LaS / CoS of Example 2 2 Scanning electron microscope (SEM) images of
[0086] Figure 6 is a scanning electron microscope (SEM) image of LaS of Comparative Example 1;
[0087] Figure 7 CoS of Comparative Example 22 Scanning electron microscope (SEM) images of
[0088] Figure 8 0.10-LaS / CoS of Example 2 2 Transmission electron microscopy (TEM) images of
[0089] Fig. 9 0.10-LaS / CoS of Example 2 2 High-resolution transmission electron microscopy (HRTEM) images of
[0090] Fig.10 is a transmission electron microscope (TEM) image of LaS of Comparative Example 1;
[0091] Fig.11 is a high resolution transmission electron microscopy (HRTEM) image of LaS of Comparative Example 1;
[0092] Fig.12 CoS of Comparative Example 2 2 Transmission electron microscopy (TEM) images of
[0093] Fig.13 CoS of Comparative Example 2 2 High-resolution transmission electron microscopy (HRTEM) images of
[0094] Fig.14 0.10-LaS / CoS of Example 2 of the present invention 2 , LaS of Comparative Example 1 and CoS of Comparative Example 2 2 Linear sweep voltammogram (LSV) of oxygen reduction reaction;
[0095] Fig.15 0.10-LaS / CoS of Example 2 of the present invention 2 Chronoamperometric response at fixed potential (0.83 V);
[0096] Fig.16 0.10-LaS / CoS of Example 2 of the present invention 2 , LaS of Comparative Example 1 and CoS of Comparative Example 2 2 Linear sweep voltammogram (LSV) of oxygen evolution reaction;
[0097] Fig.17 0.10-LaS / CoS of Example 2 of the present invention 2 At 10 mA cm -2 Chronopotentiometry curve for 38 h at a current density of ;
[0098] Fig.18 0.05-LaS / CoS of Example 12 , 0.10-LaS / CoS of Example 2 2 , 0.15-LaS / CoS of Example 3 2 X-ray diffraction (XRD) pattern;
[0099] Fig.19 0.10-LaS / CoS of Example 1 of the present invention 2 , 0.10-LaS / CoS of Example 2 2 , 0.15-LaS / CoS of Example 3 2 Linear sweep voltammogram (LSV) of oxygen reduction reaction;
[0100] Fig. 20 0.10-LaS / CoS of Example 1 of the present invention 2 , 0.10-LaS / CoS of Example 2 2 , 0.15-LaS / CoS of Example 3 2 Linear sweep voltammogram (LSV) of oxygen evolution reaction.
[0101] from Figure 1 It can be seen that the successful preparation of Example 2, Comparative Example 1 and Comparative Example 2 proves that the materials contain CoS 2 It is worth noting that the diffraction peak of LaS is very weak, which may be due to the poor crystallinity of LaS.
[0102] from Figure 2 It can be seen that Example 2, Comparative Example 1 and Comparative Example 2 all exhibit typical IV-type curves. The specific surface area of the heterogeneous interface is about twice that of a single phase.
[0103] from Figure 3 It can be seen that the pore size of Example 2 is significantly larger than that of Comparative Examples 1 and 2. This indicates that the formation of the heterogeneous interface increases the pore size and enriches the pore structure, increases the active sites, and is beneficial to the exchange of substances and electron transfer, making it exhibit stronger electrocatalytic performance than a single catalyst.
[0104] from Figure 4 It can be seen that the presence of abundant S vacancies in Example 2 provides direct evidence. The g value is about 2.003, which can be considered as a signal of sulfur vacancy defects. This is because Co (1.88) has a greater electronegativity than La (1.10), which causes S atoms to preferentially bond with Co atoms at the heterojunction interface, resulting in the formation of sulfur vacancies in the La lattice.
[0105] from Figure 5 It can be seen that the morphology of Example 2 is that the nanoparticles are loaded on the porous nanorods.
[0106] from Figure 6It can be seen that the morphology of Comparative Example 1 is particles.
[0107] from Figure 7 It can be seen that the morphology of Comparative Example 2 is a porous nanorod structure.
[0108] from Figure 8 , Fig. 9 It can be seen that: LaS / CoS 2 Successful preparation of heterojunction.
[0109] from Fig.10 , Fig.11 It can be seen that the LaS in Comparative Example 1 has low crystallinity.
[0110] from Fig.12 , Fig.13 It can be seen that the CoS of Comparative Example 2 2 Successful preparation.
[0111] from Fig.14 It can be seen that the formation of the heterogeneous interface improves the electrocatalytic performance of oxygen reduction, wherein the oxygen reduction half-wave potential of Comparative Example 1 is 0.717 V, the oxygen reduction half-wave potential of Comparative Example 2 is 0.725 V, and Example 2 has the optimal oxygen reduction half-wave potential (0.828 V) which is equivalent to the commercial catalyst Pt / C (0.848 V).
[0112] from Fig.15 It can be seen that: Example 2 2 The catalytic stability under saturated 0.1 m KOH conditions was further investigated by chronoamperometry (it). Example 2 had excellent stability, with a current retention rate of 90% after 10,000 s.
[0113] from Fig.16 It can be seen that the formation of the heterogeneous interface has a trend in the change of the catalytic activity of the oxygen evolution reaction that is consistent with that of oxygen reduction, wherein the overpotential of Comparative Example 1 is 471 mV, the overpotential of Comparative Example 2 is 333 mV, and the overpotential of Example 2 is 319 mV.
[0114] from Fig.17 It can be seen that at 10 mA cm -2 At a current density of , the oxygen evolution performance of Example 2 was stable within 38 h, and the voltage did not change significantly, indicating that the catalyst had good stability.
[0115] from Fig.18 It can be seen that the successful preparation of Example 1, Example 2 and Example 3 proves that the materials contain CoS 2 and LaS.
[0116] from Fig.19 It can be seen that: different proportions of CoS2 and LaS will affect the oxygen reduction electrocatalytic performance, wherein the oxygen reduction half-wave potential of Example 1 is 0.811 V, the oxygen reduction half-wave potential of Example 3 is 0.809 V, and Example 2 has the optimal oxygen reduction half-wave potential (0.828 V) which is equivalent to the commercial catalyst Pt / C (0.848 V).
[0117] from Fig. 20 It can be seen that: different proportions of CoS 2 and LaS will affect the oxygen evolution electrocatalytic performance, wherein the overpotential of Example 1 is 326 mV, the overpotential of Example 3 is 330 mV, and Example 2 has the lowest overpotential of 319 mV.
[0118] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface, characterized in that: The steps include: (1) dissolving a soluble cobalt source, ammonium fluoride and urea in water, heating and reacting to obtain Co(OH)F; (2) dispersing the Co(OH)F obtained in step (1) in ethanol, then adding hexamethylenetetramine and a soluble lanthanum source, stirring to dissolve, and heating to react to obtain La2O3 / Co(OH)F; (3) The La2O3 / Co(OH)F and the sulfur source obtained in step (2) are placed downstream and upstream of the protective gas flow respectively, and sintered to obtain a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface.
2. The method for preparing a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface according to claim 1, characterized in that: The soluble cobalt source in step (1) is cobalt nitrate; The molar ratio of cobalt ions, ammonium fluoride and urea in the soluble cobalt source in step (1) is 1-2:3-4:7-8; The molar volume ratio of cobalt ions to water in the soluble cobalt source in step (1) is 1-2 mmol: 50-100 mL.
3. The method for preparing the LaS / CoS2 bifunctional catalyst based on rare earth heterogeneous interface according to claim 1, characterized in that: The heating reaction time in step (1) is 5 to 8 hours; The temperature of the heating reaction in step (1) is 90-120°C.
4. The method for preparing a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface according to claim 1, characterized in that: The soluble lanthanum source in step (2) is lanthanum nitrate; The molar ratio of lanthanum ions to hexamine in the soluble lanthanum source in step (2) is 0.05-0.15:0.15-0.
45.
5. The method for preparing a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface according to claim 1, characterized in that: The mass volume ratio of Co(OH)F to ethanol in step (2) is 0.2-0.4 g: 50-100 mL; The ratio of the mass of Co(OH)F in step (2) to the molar amount of lanthanum ions in the soluble lanthanum source is 0.2 g: 0.05-0.15 mmoL.
6. The method for preparing a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface according to claim 1, characterized in that: The heating reaction time in step (2) is 5 to 8 hours; The temperature of the heating reaction in step (2) is 160-200°C.
7. The method for preparing a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface according to claim 1, characterized in that: The sulfur source in step (3) is sulfur powder; In step (3), the mass ratio of the sulfur source to La2O3 / Co(OH)F is 5 to 10:
1.
8. The method for preparing a LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface according to claim 1, characterized in that: The protective gas in step (3) is argon; The firing temperature in step (3) is 300-450° C., and the firing time is 1.5-2.5 hours.
9. A LaS / CoS2 bifunctional catalyst based on a rare earth heterogeneous interface prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the LaS / CoS2 bifunctional catalyst based on rare earth heterointerface as claimed in claim 9 in electrocatalytic oxygen evolution and oxygen reduction.